The need to provide professional development in tourism to students who minor in public relations of the B.A. in Modern Languages with Specialization in French and English, at the Department of Foreign Languages, University of el Salvador, 2019 - Calderón Lemus, Adriana Yamileth; Henríquez Miranda, Rubenia Edith; Lemus Hernández, Marisela Lissette (2024)
This research Project has as main objective to investigate the need to provide professional development in tourism to students who minor in Public Relations of the B.A. in Modern Languages with specialization in French and English, at the Department of Foreign Languages, University of El Salvador. First, it is presented an overview of tourism history in El Salvador and how it has been experiencing many changes since the Golden Era, (through) the Peace Agreements in 1992, until the improvement it has had until now. Moreover, the research team highlights how tourism has been growing in the last 10 years, and its importance for Salvadoran economy. Then, there is a review of the educational aims of the B.A. in Modern Languages and the process for updating the current Public Relations curriculum. Part of the research include to analyze the importance of updating the curriculum for the Public Relations area of the Modern Languages Major based on the needs of current labor market in the country. Afterwards, the results of the investigation are presented. It is essential to show the interest of Modern Languages students and also graduates of this major, in studying a specialization in tourism, in order to acquire extra knowledge besides being polyglot, not only to improve their skills, but also to get better job opportunities in the current market labor in the country and outside the country. Finally, some recommendations are proposed to professors that must keep updating the syllabus content, to students to be proactive and self-taught and also to authorities to offer to offer different graduation process like pre-specializations.